MRI/ultrasound fusion biopsy of the prostate compared to systematic prostate biopsy – Effectiveness and accuracy of a combined approach in daily clinical practice. Issue 154 (September 2022) - Dorfinger, Julia; Ponholzer, Anton; Stolzlechner, Michael; Lenart, Sebastian; Baltzer, Pascal; Toepker, Michael
Abstract: Purpose: The aim of this study was to compare cancer detection by targeted fusion-guided biopsy with systematic biopsy, and to evaluate the value of combined biopsy, in a daily clinical practice scenario. Furthermore, we aimed to assess the influence of previous biopsies on cancer detection. Methods: In this retrospective single-centre study, we evaluated 524 cases of combined biopsy of the prostate from October 2015 to December 2018. All men had a clinical suspicion for prostate cancer due to an elevated PSA and/or a suspicious digital rectal examination and underwent a multiparametric MRI of the prostate read by one out of 6 experienced radiologists. In all cases, fusion-guided biopsy of the prostate was consecutively followed by systematic 12-core biopsy in the same session at the same urological department performed by one out of 5 experienced urologists. Results: In 270/524 (51.5%) cases, cancer was found using combined biopsy. Systematic biopsy alone detected cancer in 205/524 (39.1%) and clinically significant cancer in 137/524 (26.1%) cases. Fusion-guided biopsy alone detected 227/524 (43.3%) and clinically significant cancer in 150/524 (28.6%) cases. A histological upgrade of the Gleason score by fusion-guided biopsy was noted in 20/270 (7.4%) of all cancers found and by systematic biopsy in 31/270 (11.5%). Of all positive cases (clinically insignificant and significant cancer), 65/270 (24.1%) were detected only by fusion-guided biopsy, whereas 43/270 (15.9%) were detected only by systematic biopsy. Conclusions: Fusion-guided biopsy can detect more cases of prostate cancers than systematic biopsy alone, especially clinically significant cancer. However, the combination of both biopsy methods improves the detection rate and can help to identify clinically significant cancer.